Pengaruh Biaya Produksi Dan Harga Jual Terhadap Pendapatan Petani Cabai Merah Di Kecamatan Doloksanggul Kabupaten Humbang Hasundutan - Noni Rozaini; Sarma Juliana Silaban (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This study aims to determine how the influence of production costs and selling prices on the income of red chili farmers in Doloksanggul District, Humbang Hasundutan Regency. This study uses secondary data taken from the BPS Humbang Hasundutan District for the 2015-2020 observation year. This study uses multiple linear regression analysis. The assumption test used is descriptive statistical analysis, normality test, autocorrelation test, multicollinearity and heteroscedasticity test. The results of this study examine the partial effect, simultaneous effect and the coefficient of determination. The entire data processing of this research uses the Eviews 9 analysis tool. From the results of this study it is known that: 1) Production costs have a positive and significant effect on the income of red chili farmers in Doloksanggul District, 2) selling price has a positive and significant effect on the income of red chili farmers in the District Doloksanggul, 3) Simultaneously production costs and selling prices affect the income of red chili farmers in Doloksanggul District, Humbang Hasundutan Regency.